2021
DOI: 10.1126/sciadv.abf6123
|View full text |Cite
|
Sign up to set email alerts
|

Predicting master transcription factors from pan-cancer expression data

Abstract: The CaCTS algorithm nominates cancer cell master transcription factors and guides a model of ovarian cancer regulatory circuitry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 94 publications
(142 reference statements)
5
46
0
Order By: Relevance
“…At the protein level, PAX8 knockdown led to an almost complete disappearance of SOX17, and SOX17 knockdown led to a substantial decrease in PAX8 levels. These results are consistent with our previously reported findings that PAX8 and SOX17 are master transcription factors that occupy regulatory elements related to their own encoding genes in ovarian cancer ( 45 ). Globally, PAX8 and SOX17 genomic binding sites colocalize within candidate active enhancers in HGSOC cell lines.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…At the protein level, PAX8 knockdown led to an almost complete disappearance of SOX17, and SOX17 knockdown led to a substantial decrease in PAX8 levels. These results are consistent with our previously reported findings that PAX8 and SOX17 are master transcription factors that occupy regulatory elements related to their own encoding genes in ovarian cancer ( 45 ). Globally, PAX8 and SOX17 genomic binding sites colocalize within candidate active enhancers in HGSOC cell lines.…”
Section: Discussionsupporting
confidence: 94%
“…Globally, PAX8 and SOX17 genomic binding sites colocalize within candidate active enhancers in HGSOC cell lines. In addition, PAX8 binds near the SOX17 gene locus, which confirms the coregulation observed in SOX17 transcript and protein levels (45). Our transcriptomic and proteomic analyses revealed that PAX8 and SOX17 commonly regulate a family of genes associated with blood vessel formation, suggesting a cooperative role in orchestrating an important proangiogenic transcriptional program in ovarian cancer.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Recent studies indicated that SOX17 may be involved in tumorigenesis, and TCGA has recently classi ed SOX17 as a mutated cancer driver gene in endometrial carcinoma (29)(30)(31)(32). Both SOX17 and PAX8 might be involved in tumorigenesis from ovarian and endometrial origins, and PAX8 promotes angiogenesis in ovarian cancer through interaction with SOX17 (33,34). Interestingly, multiple studies show SOX17 may function as a tumor suppressor in endometrial cancer and many other cancer types through inhibiting the WNT/beta-catenin oncogenic pathway, and hypermethylation of SOX17 has been linked to it repression in breast, colon, stomach, liver, and lung cancer (35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%